Travelling modernisms: the tours and acquaintances of Portuguese architects - Carvalho, Rita Almeida de (2015)
With a special interest in the nature of the interwar Portuguese dictatorial regime, this paper will analyse the path followed by contemporary European aesthetic paradigms among the Portuguese architects. The aim is to understand whether these ideas paradigms were internally absorbed and externally implicated in the built environment. To achieve this aim, architects’ travels will be reconstructed, minding that travel will be conceptualized in a broad sense, encompassing different contacts with non-Portuguese reality, such as through personal libraries, attendance to congresses, visits to exhibitions, study tours, vacations, education abroad, and acquaintance with foreign architects. This knowledge is expected to enlighten whether certain right-wing dictatorial political models, like Nazism and Fascism, were apprehended and embodied by architects involved in public buildings' commissions; or, conversely, if the aesthetic influence of Portuguese long-standing allies, like the United Kingdom and France, was still dominant. Stretching the argument, one might event wonder if the autarchy's political claims during the Portuguese regime were also extended to the architectural field. All in all, the research's initial hypothesis was that some architects were more cosmopolitan than acknowledged. In proving it, the emphasis put by the art history and architectural history on Portuguese atavism loses strength, as architects would have been inspired and influenced by as many as the existent European regimes.